Land Use, Temperature, and Nitrogen Affect Nitrous Oxide Emissions in Amazonian Soils - Lage Filho, Nauara M.; Cardoso, Abmael da S.; Azevedo, Jorge C. de; Faturi, Cristian; Silva, Thiago C. da; Domingues, Felipe N.; Ruggieri, Ana C. [UNESP]; Reis, Ricardo A. [UNESP]; Rêgo, Aníbal C. do (MDPI, 2022)
Nitrous oxide (N2O) is one of the main gases emitted from soils, and the changes in land use in the Amazon may alter gas emission patterns. The objective of this study was to evaluate the effects of land use, temperature, and nitrogen on N2O emissions in soils in the Amazon. For this, three treatments randomized, with five repetitions, were incubated to quantify N2O emissions: (i) three different land uses (wet rainforest, pasture, and agriculture); (ii) different temperatures (25, 30, 35, and 40◦C); and (iii) different nitrogen additions to the soil (0, 90, 180, and 270 kg of N ha−1). Our results show that land use alters the flux of N2O, with the highest emissions observed in agricultural soils compared to that in forest and pasture areas. The change in soil temperature to 30◦C increased N2 O emissions with land use, at which the emission of N2O was higher in the pasture and agriculture soils. Our results showed that the emission of N2O in the soil of the Amazon rainforest was low regardless of the temperature and nitrogen treatment. Therefore, the change in land use alters the resilience of the ecosystem, providing emissions of N2 O.
Keywords: Amazon deforestation arc; greenhouse gas; land-use change; N2 O emission; wet rainforest